Transformation of glycosyltransferase dnrs and auxiliary DNRQ genes into the Streptomyces peucetius MH9.2 for the enhance of doxorubicin production - Thuy, Ta Thi Thu; Hoang, Nguyen Huy (Vietnam Journal of Biotechnology, 2018)
Doxorubicin antibiotic produced by Streptomyces peucetius is a very crucial antibiotic with a large spectrum used as an anticancer drug and in clinical treatment. Production of doxorubicin from wild type strain by microbiological fermentation process is nomally very low yield and limited. The enhancement of doxorubicin production (DXR) by the genetically engineering of the auxiliary genes involved in the pathway of doxorubicin biosynthesis from Streptomyces peucetius has being focused by many research groups. The gene cluster responsible for biosynthesis of doxorubicin had been isolated, sequenced and characterized. Among them, the dnrQ and dnrS genes belong to the gene cluster encoded for the glycosyltransferase and helper enzymes, which are responsible for attachment of sugar moiety to -rhodomycinon intermediate and regulation of doxorubicin production, respectively. In this research, the dnrQ and dnrS genes were isolated and cloned in the p25.1 vector containing the strong promoter (ermE*) to generate the p25.1QS as a recombinant vector. The obtained plasmid was transferred into the host strain Streptomyces peucetius MH9.2 by the protoplast transformation method to generate the S. peucetius MH9.2SQ strain. Doxorubicin production from the recombinant S. peucetius MH9.2SQ and the parent strain were extracted and purified by using chlorofrom and methanol solvents. The products were confirmed by HPLC, LC-mass analysis and antibacterial bioassay. The results showed that the over production of doxorubicin was accumulated by the recombinant strain from the fermentation broth. In the S. peucetius MH9.2SQ, the doxorubicin productivity was 3.1 to 3.6 folds higher than in the parent strain. This recombinant strain could be a potential candidate for further research in enhancement and larger biomass scale of DXR production.